Occupying Urban Memory: The Construction of Jerusalem in the Tower of David Museum’ - Janson, Torsten (Urban Transformations and Urban Histories, Malmö, Sweden, 2024-05-15 - 2024-05-17, 2024)
This paper will discuss the memory-political narrative of the Tower of David Museum, located in the Old City of Jerusalem/al Quds. As part of a current research project on the role of urban imageries and spaces in constructions of Middle Eastern nationalisms, it will explore how the museum is part and parcel of the interwoven historiographic, cultural, and political quest to normalise and obscure the realities of Israel’s occupation of East Jerusalem. The paper is based on two periods of fieldwork in museums and other memory spaces in the city, exploring historical heritage sites as well as newly constructed urban memory spaces, in the context of the horrific war (and hostage situation) currently raging in Gaza. The museum building is unique in several ways, as an archeological site as well as a longstanding object for historical, religious and political imaginaries. In reality a citadel, already in Byzantine times it became subject to vivid religious imaginations, misconstrued as the site of the “Tower of David”. The misconception only deepened when the crusaders ironically mistook the Citadel’s minaret as the proverbial “tower”. Despite the inaccuracy, the name stuck, and the “Tower” has ever since been a prominent visual-political symbol for the city, from medieval times to modernity. After the 1967 occupation of Eastern Jerusalem, the citadel was excavated, and reopened 1989 as the official history museum of the city. Since then the museum has been part and parcel of a political/military/cultural claim on “the reunited city”, in Israeli national discourse (while Palestinian claims are obscured). This paper will devote attention to such dynamics between the spatial processes in the city and the culturally construed imaginations of the city; dynamics for which representational spaces such as the Tower of David Museum play a central role.